2010
DOI: 10.1021/la103428g
|View full text |Cite
|
Sign up to set email alerts
|

Giant Phospholipid/Block Copolymer Hybrid Vesicles: Mixing Behavior and Domain Formation

Abstract: Lipids and block copolymers can be individually assembled into unsupported, spherical membranes (liposomes or polymersomes), each having their own particular benefits and limitations. Here we demonstrate the preparation of microscale, hybrid "lipopolymersomes" composed of the common lipid POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphatidylcholine) and the commercially available copolymer PBd-b-PEO (polybutadiene-b-poly(ethylene oxide)) with the goal of incorporating the advantageous qualities of the unitary s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
205
3
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(221 citation statements)
references
References 27 publications
8
205
3
5
Order By: Relevance
“…Studies reported to date on hybrid vesicles have not yielded detailed information on the efficiency of hybrid vesicle formation in bulk solution [14][15][16][17][18][19][20][21]. Flow cytometry has been demonstrated as a useful tool to study vesicle populations [23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies reported to date on hybrid vesicles have not yielded detailed information on the efficiency of hybrid vesicle formation in bulk solution [14][15][16][17][18][19][20][21]. Flow cytometry has been demonstrated as a useful tool to study vesicle populations [23].…”
Section: Resultsmentioning
confidence: 99%
“…It may be concluded that liposomes and polymersomes have their own particular benefits and limitations, which is why the preparation of hybrid membranes consisting of phospholipids and block copolymers is attracting increasing attention [14][15][16][17][18][19][20][21]. In this way, the robustness and chemical versatility of polymersomes can be combined with the softness and biocompatibility of liposomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For POPC/PBut 2.5 ‐ b ‐PEO 1.3 aGHUV we found D = 1.8 ± 0.50 µm 2 s −1 for DOPE‐rhod at 25 °C. Under the same experimental conditions, the diffusion coefficient for DOPE‐rhod in pure PBut 2.5 ‐ b ‐PEO 1.3 giant vesicles was found to be D = 0.46 ± 0.055 µm 2 s −1 and it has been shown that for pure POPC giant vesicles D = 9.8 ± 1.7 µm 2 s −1 61. Therefore, as for GHUV, an intermediate diffusion coefficient value is found, and shows that despite the asymmetric character of the membrane, the lipid lateral diffusion coefficient is lowered by the copolymer chains, suggesting some interdigitation between lipids and copolymer chains in the membrane.…”
Section: Resultsmentioning
confidence: 87%